Effect of clove flower extract (Syzygium aromaticum) administration timing on skeletal muscle damage induced by eccentric exercise: An in vivo study - Ningrum, Tyas Sari Ratna; Doewes, Muchsin; Indarto, Dono; Cilmiaty, Risya; Kristiyanto, Agus; Widyaningsih, Vitri (Narra J, 2025)
Eccentric exercise often leads to oxidative stress, inflammation, and muscle damage that impair athletic performance. To counter these adverse effects, clove flower extract (Syzygium aromaticum) offers promising potential as a natural remedy to promote muscle repair with its potent antioxidant and anti-inflammatory properties. The aim of this study was to assess the effects of clove flower extract administration timing on oxidative stress and inflammatory responses in skeletal muscle damage induced by acute eccentric exercise in mice. This study used a post-test-only control group design, involving 35 male mice (Mus musculus, Balb/c) randomly divided into five groups: a healthy control group (HC) with no exercise and no treatment, a negative control group (NC) with exercise but no treatment, and three treatment groups: T1, T2, and T3 (clove flower extract 24 hours before exercise, immediately after exercise, and 24 hours after exercise, respectively). The treatment groups received a single dose of clove flower extract (500 mg/kg body weight). The skeletal muscle damage of mice was collected for the NADPH oxidase (NOX) and superoxide dismutase (SOD) activities using spectrophotometry, and toll-like receptor 4 (TLR4) and interleukin-8 (IL-8) measurements using enzyme-linked immunosorbent assay (ELISA). Moreover, the skeletal muscle damage was analyzed through the histopathological method. Data were analyzed using one-way analysis of variance (ANOVA) followed by Fisher's least significant difference (LSD) tests as a post hoc test. The result showed that clove flower extract significantly reduced NOX activity (p=0.049) and IL-8 levels (p=0.032), and increased SOD activity (p=0.001) while not significantly affecting the TLR4 levels (p=0.532). Moreover, the results showed a significant reduction in muscle damage (p=0.001). The study highlights that the administration of clove flower extract (500mg/kg bw) can be given 24 hours before, immediately after exercise, or 24 hours after exercise to prevent muscle damage.